2009
DOI: 10.1016/j.engappai.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An iterative agent bidding mechanism for responsive manufacturing

Abstract: In today's market, the global competition has put manufacturing businesses in great pressures to respond rapidly to dynamic variations in demand patterns across products and changing product mixes. To achieve substantial responsiveness, the manufacturing activities associated with production planning and control must be integrated dynamically, efficiently and cost-effectively. This paper presents an iterative agent bidding mechanism, which performs dynamic integration of process planning and production schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Other researchers reported that, in many cases, simulation reaches its limits because it does not allow to play certain scenarios where the behaviour of the system changes (Powell et al 2001;Ören et al 2014). In order to improve the behaviour of the system or to predict the occurrence of influencing random events, several researchers recommended to add some optimization algorithms into the simulation process (Lim et al 2009;Powell 2005). In Wu et al (2003) and Powell (2008), the authors adopted the optimization simulation method and used rough dynamic programming to solve various optimization problems.…”
Section: Related Workmentioning
confidence: 99%
“…Other researchers reported that, in many cases, simulation reaches its limits because it does not allow to play certain scenarios where the behaviour of the system changes (Powell et al 2001;Ören et al 2014). In order to improve the behaviour of the system or to predict the occurrence of influencing random events, several researchers recommended to add some optimization algorithms into the simulation process (Lim et al 2009;Powell 2005). In Wu et al (2003) and Powell (2008), the authors adopted the optimization simulation method and used rough dynamic programming to solve various optimization problems.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the PA relies on the process plan provided to make a large fraction of its decisions. For example, once initialized by the system, a PA must understand the surrounding manufacturing environment [40], [41]. The PA can use the process plan to build an update version of the manufacturing environment in the vicinity of the associated physical part by querying the availability of the next desired features from the RAs.…”
Section: F Agent Initializationmentioning
confidence: 99%
“…An inceptive application of the SIoT focuses on trying to improve industrial system performance by making use of distributed decision-making with the help of the IoT, giving a social dimension to industrial assets. For example, the attempts of using distributed decision-making in production scheduling, maintenance scheduling, and inventory management can be found in (Lim et al 2009), (Zhou et al 2004), and (Jiang and Sheng 2009) respectively.…”
Section: Literature Reviewmentioning
confidence: 99%